The effect of balanced N, P, K, Ca, Mg fertilizer on soil and leaf nutrient and its correlation with growth and corn yield (Zea mays L.) - Syamsiyah, Jauhari; Hartati, Sri; Rahmanisa, Lily; Maro’ah, Siti; Herdiansyah, Ganjar (Journal of Aridland Agriculture, 2024)
Fertilization in agricultural cultivation is important in increasing the supply of necessary nutrients for plants to achieve high yield and quality. This study aims to examine the balance of N,P,K,Ca, and Mg against nutrients in soil and plants and its correlation with the growth and yield of corn. There were 9 treatments of N, P, K, Ca, Mg fertilizer balance used, namely: control (A) and 1: 1: 1: 0: 0 (B); 0.25: 0.25: 0.25: 1: 1 (C); 0.5: 0.5: 0.5: 1: 1 (D); 0.75: 0.75: 0.75: 1: 1 (E); 1: 1:1: 1: 1 (F); 0.75: 0.75: 0.75: 0.25: 0.25 (G); 0.75: 0.75: 0.75: 0.5: 0.5 (H); 0.75: 0.75: 0.75: 0.75: 0.75 (I). Parameters observed included nutrients N, P, K, Ca, and Mg in soil and leaf, plant height, stem diameter, number of leaves, cob weight with and without husks, and cob length and diameter. The results showed that nutrient balance significantly affected nutrient levels in soil and leaf, plant growth, and yield of corn. N, P, K, Ca, Mg Fertilizer application with ratio 0.5: 0.5: 0.5: 1: 1 (D) increased soil N 100%, P 40%, K 108.33%, Ca 28.08%, Mg 30.17% higher than the control and plant leaf N, P, K, Ca, Mg about 101.60%, 12.50%, 10.13%, 50.98%, 101.41% respectively, thus providing higher growth and yield. There was a significant correlation between plant height with leaf N and K, stem diameter correlated with leaf Ca, and number of leaves correlated with Mg in corn leaf. Meanwhile, yield correlated with P.